2020
DOI: 10.1002/adma.202002873
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Polarization‐Resolved Second‐Harmonic‐Generation Microscopy of Glycine Microneedles

Abstract: amino acids, peptides, and proteins offers a noncontact, label-free and nondestructive method of obtaining a better understanding of disease processes both in vitro and in vivo. SHG has further applications in nanoscale characterization, [5] measurement of field-induced carrier motion in photonic devices, [6] and in the development of micro/nanoscale lasers. [7] Qualitative comparison of SHG conversion efficiency suffers from not having a clear benchmark of quantitative values of tensor elements. First princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…The γ-polymorph has also remarkable non-linear optical properties and can be used for second harmonic generation (SHG). [278][279][280][281] This property can also find biomedical applications, such as diagnostic imaging. SHG can provide disease diagnosis through characterization of biological building blocks.…”
Section: Physical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The γ-polymorph has also remarkable non-linear optical properties and can be used for second harmonic generation (SHG). [278][279][280][281] This property can also find biomedical applications, such as diagnostic imaging. SHG can provide disease diagnosis through characterization of biological building blocks.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…A comparison of the SHG susceptibility tensors of βand γ-phase glycine microneedles gave the maximum nonlinear susceptibility coefficients d 33 = 15 pm V À 1 for the β and d 33 = 5.9 pm V À 1 for the γ phase. [278] One of the major advantages of glycine-based materials is their ability to biodegrade without polluting the environment or poisoning a living organism. Electronics wastes (e-wastes) are the major concern in the rapid expansion of smart/ wearable/portable electronics in modern high-tech society.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…On a completely different scale, glycine has been found in the interstellar medium (Kuan et al, 2003;Ioppolo et al, 2021) and in the comas of comets and meteorites, (Elsila et al, 2009;Altwegg et al, 2016) thus providing evidence of the panspermia hypothesis (Wesson, 2010). As for the functional physical properties of crystalline glycine, they largely depend on the supramolecular packing of its molecules into three main polymorphs (α, β, and γ), resulting in different crystallographic structures (Heredia et al, 2012;Guerin et al, 2017;Gleeson et al, 2020;Boldyreva, 2021). It has been a long time established that the α-phase is centrosymmetric (space group P2 1 /n), in which only surface piezoelectricity and pyroelectricity may exist via doping or water incorporation (Piperno et al, 2013;Meirzadeh et al, 2018;Dishon et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is unique amongst biomolecular crystals in that the predicted electronic and ionic contributions to the piezoelectric tensor are both high but of opposite polarity, resulting in these reduced values. This also explains why valine has a low piezoelectric response, but high non-linear optical performance (Moitra and Kar, 2010), as we have recently demonstrated that the second harmonic generation capabilities of small biomolecular crystals correlates to the electronic contribution to the piezoelectric tensor only (Gleeson et al, 2020).…”
Section: Resultsmentioning
confidence: 82%